Concomitant imatinib and ibrutinib in a patient with chronic myelogenous leukemia and chronic lymphocytic leukemia. Issue 6 (24th April 2017) - Shea, Lauren K.; Mikhail, Fady M.; Forero‐Torres, Andres; Davis, Randall S.
Key Clinical Message: The availability of kinase and other small‐molecule inhibitors to treat hematologic malignancies is increasing. Accordingly, novel regimens that employ these therapeutics are rapidly evolving. Herein we report the safe and effective administration of two targeted kinase inhibitors in a patient with concomitant chronic myelogenous leukemia and chronic lymphocytic leukemia. Abstract : The availability of kinase and other small‐molecule inhibitors to treat hematologic malignancies is increasing. Accordingly, novel regimens that employ these therapeutics are rapidly evolving. Herein we report the safe and effective administration of two targeted kinase inhibitors in a patient with concomitant chronic myelogenous leukemia and chronic lymphocytic leukemia.